SYSTEM INTERACTION MODEL OF ECOLOGICAL INSURANCE ENTITIES - Vladislav R. MURATOV (Advanced Engineering Research, 2010)
Ecological insurance programmes selected into the individual module of the insurance entities interaction in the general insurance system are considered. Development of the national ecological insurance system requires its governance model building based on the specific exploitation of certain natural resources and hazardous productions control.